1980
DOI: 10.1007/bf00150582
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of H? spicules according to spectral observations at various heights of the solar chromosphere

Abstract: Almost simultaneous height sequences of 69 spicules in the Ha line have been studied. The spectra are obtained at six heights during 6 s on the east side of the solar disk with the 53-cm Lyot coronagraph of Abastumani Astrophysical Observatory.Radial velocities V,, total intensities or equivalent widths W, full widths at half maximum of intensity (FWHM) at all heights are determined (about 300 profiles of the Ha line). It is found that:(1) Absolute values of radial velocities increase linearly with the height … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

1981
1981
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…The main reason for these discrepancies are due to the fact that observations of spicules at various heights simultaneously are related to instrumental difficulties. Kulidzanishvili (1980) studied almost simultaneously height sequences of 69 spicules in the Hα line. He claimed that absolute values of LOS velocities increase linearly with height and that no variation of the sign of the LOS velocity along individual spicules is observed.…”
Section: Spicule Inclinationmentioning
confidence: 99%
“…The main reason for these discrepancies are due to the fact that observations of spicules at various heights simultaneously are related to instrumental difficulties. Kulidzanishvili (1980) studied almost simultaneously height sequences of 69 spicules in the Hα line. He claimed that absolute values of LOS velocities increase linearly with height and that no variation of the sign of the LOS velocity along individual spicules is observed.…”
Section: Spicule Inclinationmentioning
confidence: 99%
“…As for the fast components, we assume that their surrounding magnetic field is nearly parallel to the LOS, so the Alfvén waves will not contribute to line-broadening, agreeing with their narrow widths even if they are composed of multiple finer threads. Kulidzanishvili (1980) reported the oscillations of the radial velocities of limb spicules with the period of 3-7 min. However, their amplitudes were less than 10 km s −1 , which are too small to contribute to our observed line-widths.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…They suggested that the Hα spicules have temperature of 6000 K and nonthermal velocities of ∼25 km s −1 . Follow-up spectroscopic observations of limb spicules under much better seeing conditions were done by Kulidzanishvili (1980) with the 53-cm Lyot coronagraph of Abastumani Astrophysical Observatory and by Hasan & Keil (1984) with Sacramento Peak VTT. From the study of line-of-sight (LOS) velocity and line-width distribution along the axis of spicules, they got a result that, in majority of spicules, the Hα linewidth does not change spatially along the axes of spicules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23]. Ïîçaeå, 3-7 -ìèíóòíûå (ïèê íà 5 ìèí) êîëåáàíèÿ ñïèêóë îòìå÷åíû â [24][25][26][27][28][29]. Êîëåáàíèÿ áûëè èçó÷åíû De Pontieu, Erdélyi & James [30], Khutsishvili et al [31,32] è äðóãèìè.…”
unclassified